Low-intensity pulsed ultrasound enhances neurite growth in serum-starved human neuroblastoma cells - Ye, Xuanjie; Wang, Zitong; van Bruggen, Rebekah; Li, Xin-Min; Zhang, Yanbo; Chen, Jie (Frontiers in Neuroscience, 2023)
Introduction Low-intensity pulsed ultrasound (LIPUS) is a recognized tool for promoting nerve regeneration and repair; however, the intracellular mechanisms of LIPUS stimulation remain underexplored. Method The present study delves into the effects of varying LIPUS parameters, namely duty cycle, spatial average-temporal average (SATA) intensity, and ultrasound amplitude, on the therapeutic efficacy using SK-N-SH cells cultured in serum-starved conditions. Four distinct LIPUS settings were employed: (A) 50 mW/cm2, 40%, (B) 25 mW/cm2, 10%, (C) 50 mW/cm2, 20%, and (D) 25 mW/cm2, 10%. Results Immunochemistry analysis exhibited neurite outgrowth promotion in all LIPUS-treated groups except for Group D. Further, LIPUS treatment was found to successfully promote brain-derived neurotrophic factor (BDNF) expression and enhance the phosphorylation of extracellular signal-regulated kinase (ERK)1/2, protein kinase B (Akt), and mammalian target of rapamycin (mTOR) signaling pathways, as evidenced by western blot analysis. Discussion The study suggests that the parameter combination of LIPUS determines the therapeutic efficacy of LIPUS. Future investigations should aim to optimize these parameters for different cell types and settings and delve deeper into the cellular response mechanism to LIPUS treatment. Such advancements may aid in tailoring LIPUS treatment strategies to specific therapeutic needs.